Gender-based violence and associated factors among female sex workers in Ethiopia. Evidence from The National Bio-behavioral Survey, 2020 - Debel, Lemessa; Ayalew, Jemal; Abdella, Saro; Bulti, Jaleta; Bejiga, Birra; Wariso, Fayiso Bati; Belete, Wudinesh; Habtesilase, Abebe; Lulseged, Silesh (Frontiers in Public Health, 2024)
Background: Gender-based violence (GBV) is usually defined as unequal power relations between men and women, which poses a widespread public health problem. The study evaluated the prevalence and factors associated with GBV among female sex workers(FSWs) in Ethiopia. Method: We used cross-sectional bio-behavioral data collected using respondent-driven sampling (RDS) in 2020 from 16 towns in Ethiopia. Descriptive statistics was analyzed to summarize the study population characteristics and prevalence of GBV, and a multilevel logistic regression model was applied to identify associated factors for GBV. A p-value of ≤0.05 was used as a threshold for statistical significance. Result: Of 6085 participants, 28.1% had experienced GBV during the last 12 months, among which; 12.7% and 22.3% experienced physical and sexual violence, respectively. FSWs aged 15–24, and 25–34 than those 35 years or more, had a nonpaying than paying partners, had 31–60, 61-90, and over 91 than those had less than 30 paying partners, ever had anal sex than those not, condom failure than those not, , mobile female sex workers when compared with those not mobile at the different town; 3–5 and ≥6 years than those less than 3 years stayed in selling sex, street-based, and multiple places selling sex than those used other venues were significantly associated with GBV. Conclusion: Gender-based violence is a substantial problem among FSWs in Ethiopia, with significant implications for program planning on prevention and response to mitigate the occurrence and impact of GBV among FSWs.